Hypocrites of old or water carriers of new era and their invisible victims: Rethinking corporate social responsibility - Đurić-Kuzmanović Tatjana (Temida, 2014)
Modern business results indicate more clearly the increasing negative effects which corporation business strategies, exclusively oriented to making profit, have on population and the planet. Corporative social responsibility (CSR) as a complex system of business and management that balances among the economic, social and ecological objectives of stakeholders is increasingly recommended as an alternative or integral part of modern business and development strategies. The role and effectiveness of CSR is becoming the subject of intense debate between all those who interpret it as hypocritical mercy of employers and those who see it as a possible paradigm shift in thinking about more effective social and business development strategies. In this paper the role of CSR is discussed from the perspectives of Feminist development economics and Another development strategies, primarily in relation to the safety of employees and the population. The aim of this paper is to recognise the role of CSR in reproducing the increasing number of, from the neo-liberal discourse, still insufficiently visible victims of neoliberal capitalism using comparative theoretical analysis. The paper further aims to emphasise the need to redefine the action, evaluation and measurement of CSR in terms of New economy 2 and Another development.